Relationship between antibiotic resistance, efflux pumps, and biofilm formation in extended-spectrum β-lactamase producing Klebsiella pneumoniae. (17th November 2018) - Türkel, İbrahim; Yıldırım, Tuba; Yazgan, Burak; Bilgin, Melek; Başbulut, Eşe
Abstract : Klebsiella pneumoniae is an important pathogen both in community and hospital environment. In this study, we aimed to determine the antibiotic susceptibilities, expression levels of AcrA, ketM, kdeA, kpnEF, and kexD genes related to efflux pump and biofilm formation in 100 extended-spectrum β-lactamase producing Klebsiella pneumoniae . The relative expression levels of AcrA, ketM, kdeA, kpnEF, and kexD were determined by quantitative real-time PCR and biofilm formation was screened by microtiter plate assay. Based on CLSI breakpoints, zone diameters showed that 72% of isolates were resistant to ceftazidime, 79% to aztreonam, 54% to ciprofloxacin, 32% to ertapenem, 74% to tobramycin, 65% to tetracycline and all isolates were resistant to ampicillin, ceftriaxone, and cefotaxime. The relative expression of AcrA was upregulated in ciprofloxacin susceptible isolates and also upregulation of newly described efflux pump, kexD, was correlated with tobramycin and aztreonam resistance. A significant correlation was observed between resistance-nodulation-division and single-type efflux pumps. On the other hand, ciprofloxacin susceptible isolates formed stronger biofilms than resistant isolates. The up or down regulation of efflux pumps didn't enhance biofilm formation capacity.